Error‐Controlled Model Order Reduction of Second Order Systems with Adaptive Choice of Shifts and Order. Issue 1 (December 2014) - Panzer, Heiko K. F.; Wolf, Thomas; Lohmann, Boris
Abstract This contribution summarizes a novel approach to error‐controlled model order reduction of second order systems, i. e. a new way to find a reduced order model of specified approximation quality. To this end, starting from a particular state space realization of the model, one performs multiple reduction steps and increments the reduced model until (computationally affordable) rigorous global error bounds fall below the prescribed limit. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)